Exploring Spatial Patterns at “Nørholm”, a Metal-rich Site by the Limfjord, Northern Denmark: on Metal Detection, Settlement History and the Development of Land Exploitation - Christiansen, Torben Trier (Danish Journal of Archaeology, 2020)
Private metal detecting currently has a massive impact on North European archaeology. However, due to the poor contextual data of the finds, the unsystematic search methods and not least insufficient excavations at detected sites, the spatial understanding of the sites and the knowledge potentially to be gained from metal finds from the plough layer is still limited. This paper presents a programme of investigations at the most productive detector site in Jutland, “Nørholm”, which offers a framework for interpretation of distribution patterns of the metal finds recovered over more than two decades by private detectorists. It is argued that overall changes in settlement patterns as well as changes in the associated field systems are major dynamics behind the spread of metal detector finds. A detailed, chronological mapping of the distribution of finds thus allow a reconstruction of the history of settlement and land use during the Late Iron Age and the Middle Ages.